Выражения 1)(х+2)(x-2)+(2-x)^2-5(9-x) 2)(a+2)^2-(3a+2)(3a-2)-6(a-2) 3)3,4x^2y*(-5x^3y^2)^2 4)-5a^2bc*(4a^2b^4)^3 (после значка ^ идёт степень)

oksanademyanov oksanademyanov    1   01.07.2019 00:40    0

Ответы
славик55 славик55  24.07.2020 13:25
(x+2)(x-2)+(2-x)^2-5(9-x)=
x^2-4+4-4x+x^2-45+5x=2x^2+x-45

(a+2)^2-(3a+2)(3a-2)-6(a-2)=
a^2+4a+4-(9a^2-4)-6a+12=
a^2+4a+4-9a^2+4-6a+12=-8a^2-2a+20

3,4x^2y(-5x^3y^2)^2= 3,4x^2y*25x^6y^4=85x^8y^5

-5a^2bc(4a^2b^4)^3=
-5a^2bc*64a^6b^12=320a^8b^13c
надеюсь все понятно и нет ошибок
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра